Pengembangan Instrumen Pengukuran Data Alumni Sesuai dengan Kriteria AUN-QA: Analisis Uji Validitas - Fanny Rahmasari; Mukhlidi Muskhir (Universitas Negeri Padang, 2020)
This study aims to produce a valid tracer study instrument to monitor graduates of the Electrical Engineering Education Study Program. This type of research and development uses the Borg and Gall model of research and development by limiting only 5 stages. To see whether the tracer study instrument is valid, an expert test is conducted. The results of the study obtained an average validity by material experts with the valid category. From the research results it can be concluded that the instruments developed in accordance with Aun-Qa's criteria can be distributed to graduates of the Electrical Engineering Education Study Program. Based on the research results of the alumni of Electrical Engineering Education, most of the graduates completed their study period between 3.5 and 4 years with a very satisfying GPA predicate. The time span required for graduates or alumni to wait for the work period is 1 to 7 months. The first income earned by graduates or alumni is an average of 1 million. Thus, many graduates of the Electrical Engineering Education Study Program work in the field of education and can be said to be quickly absorbed in the world of work and job prospects in the industrial sector can be said to be good.